Observation on a human intentional poisoning case by the organophosphorus Insecticide fenthion - Brunetto, María del Rosario; Burguera, José Luis; Burguera, Marcela; Villegas, Fanny; Bastidas, Carmen (Investigación Clínica, 2013)
A case of acute poisoning by oral ingestion of fenthion 1s reported. Plasma cholinesterase activity and fenthion whole blood concentration were tbroughly evaluated during the therapeutic intervention that consisted in administration of atropine. toxogonine and fresh plasma. Correlation studies between clinical signs, cholinesterase activity and fenthion levels revealed that pChE activity was not as helpful as the patient's clinical status in determining when the atropine infus10n could be stopped. Morever pChE was also useless in signaling sudden relapses. It 1s concluded, based on this case, that supportive care combined with antidotal therapy remáins the cornerstone of treatment specially in severe acute poisoning cases.